Constructivism: Its Implications for Language Teaching and Second-Language Acquisition - John, Philpo (Papers in Education and Development, 2018)
This article presents the term constructivism both as a theory of learning and as a philosophical concept. In this regard, principles and assumptions of the theory of constructivism as propounded by its proponents, viz.: Immanuel Kant, Jean Piaget and Lev Vygotsky, have been revisited to establish its link with language teaching and second-language acquisition. To bring the implications to light, this article makes use of five selected key theoretical [case] studies underpinning the connection between constructivism and language teaching and second-language acquisition. The analysis indicates certain key observations. One is that language teaching-learning and language acquisition are both activities that involve interactions between the teacher and the learner. However, to create knowledge, the teacher is required [enjoined] to facilitate and guide learners to ' discover ' . In accordance with the constructivist theory of learning, learning is not only individual but also active, as the creation of knowledge is socially constructed. In this way, the language learner must be enabled to independently learn and socially interact with others in order to acquire the linguistic knowledge and skills that a learner will eventually use to interact with others in the real world. These practices are informed by constructivism as it deals with the nature of knowledge and the way knowledge is created. The article, therefore, concludes that in language teaching and learning, both nature and nurture should be supported by creating an enabling environment in which linguistic knowledge is constructed. Key words: Constructivism, Language; Language teaching; Second-language acquisition; Constructivist Philosophy